2000
DOI: 10.1128/jvi.74.3.1132-1139.2000
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific TT Viruses and Cross-Species Infection in Nonhuman Primates

Abstract: Viruses resembling human TT virus (TTV) were searched for in sera from nonhuman primates by PCR with primers deduced from well-conserved areas in the untranslated region. TTV DNA was detected in 102 (98%) of 104 chimpanzees, 9 (90%) of 10 Japanese macaques, 4 (100%) of 4 red-bellied tamarins, 5 (83%) of 6 cotton-top tamarins, and 5 (100%) of 5 douroucoulis tested. Analysis of the amplification products of 90 to 106 nucleotides revealed TTV DNA sequences specific for each species, with a decreasing similarity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 40 publications
4
45
0
Order By: Relevance
“…Human and simian TTVs share closely related genome organization and presumed transcriptional profiles, showing nearly 85% sequence similarity. However, it is now well established that TTV variants in nonhuman primates are species-specific [5,23,24,35,58] and that TTVs from macaques and tamarins are increasingly divergent from TTV variants infecting humans and chimpanzees [35]. Recent evidence shows that simian TTV can infect humans, as it has been observed that approximately 10% of Japanese patients with liver diseases are infected with simian TTV, although the mode of transmission of the infection from animals to humans has not been demonstrated [59].…”
Section: Animal Ttvsmentioning
confidence: 99%
“…Human and simian TTVs share closely related genome organization and presumed transcriptional profiles, showing nearly 85% sequence similarity. However, it is now well established that TTV variants in nonhuman primates are species-specific [5,23,24,35,58] and that TTVs from macaques and tamarins are increasingly divergent from TTV variants infecting humans and chimpanzees [35]. Recent evidence shows that simian TTV can infect humans, as it has been observed that approximately 10% of Japanese patients with liver diseases are infected with simian TTV, although the mode of transmission of the infection from animals to humans has not been demonstrated [59].…”
Section: Animal Ttvsmentioning
confidence: 99%
“…We similarly excluded the C-terminal region sequence beyond amino acid 288 as sequences of non-human primates could not be defensibly aligned with each other or with primatederived TTV sequences. The tree showed that chimpanzee TTMDV is a virus species that is phylogenetically distinguishable from TTVs and TTMVs of human and chimpanzee origin as well as TTVs of macaque, douroucouli, tamarin, tupaia, dog, cat and pig, whose entire genomic sequence has thus far been determined (Okamoto et al, 2000a(Okamoto et al, , b, 2001. Of note, chimpanzee TTMDVs were clearly separate from human TTMDVs, while chimpanzee TTVs (Pt-TTV6, s-TTV.CH65-1, s-TTV.CH65-2 and s-TTV.CH71) and chimpanzee TTMV (Pt-TTMV8-II) were interspersed with human TTVs and human TTMVs, respectively.…”
Section: Comparison Of the Three Pt-ttmdv Isolates With Each Other Anmentioning
confidence: 99%
“…Our previous study using a newly developed PCR method revealed high frequencies of viraemia with TTV (99.2 %), TTMDV (82.4 %) and TTMV (89.7 %) among apparently healthy subjects of 1-81 years of age. Additionally, dual or triple infection of these three anelloviruses was seen frequently, even among infants (Ninomiya et al, 2008).Infection with TTV is not restricted to humans; various animal species including non-human primates, tupaias, livestock and some companion animals carry a wide range of highly divergent TTV-like viruses (Inami et al, 2000;Okamoto et al, 2000a Okamoto et al, , b, 2001Okamoto et al, , 2002Thom et al, 2003). Notably, and in contrast with other non-human primates and other animal species, chimpanzees are also infected with TTMVs (Okamoto et al, 2000b).…”
mentioning
confidence: 99%
“…At present, epidemiological studies suggest that TTV is mainly transmitted by blood [13][14][15] ; blood products [16] and body fluid routes [13,17] , it can also be transmitted by mother-to-child vertical [18] and horizontal [19,20] route , fecal-oral route [9,15,21] and sexual route [22] . The infection rate of TTV DNA varies largely in healthy population and patients with liver diseases, but generally, it is higher in patients than in healthy donors [7,[23][24][25][26] . The discovery of TTV once put a light on the etiological diagnoses of hepatitis cases of unknown etiology, unfortunately, the pathogenicity and clinical significance of TTV remain doubtful at this time [25,[27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…TTV is an unenveloped, single-stranded and circular DNA virus, which consists of 3852 nucleotides and most closely resembles the members of the Circoviridae family [1][2][3] . Meanwhile, different studies suggested that TTV genotypes were so much and could vary frequently [4][5][6][7][8] . It is believed that TTV belongs to hepadnavirus and replicates chiefly in the liver [9][10][11] , however, some researchers think that the replication site is in the bone marrows rather than in the livers [12] .…”
Section: Introductionmentioning
confidence: 99%